Analysis of the Effect of Financial Ratios on Financial Performance at PT PLN (Persero) - Desliyadi, Zahra Ramadhania; Mareta, Sigit; Lestari; Doktoralina, Caturida Meiwanto; Sulistiyowati, Rini (Social and Economic Bulletin, 2025)
This study aims to analyze the effect of financial ratios on the financial performance of PT. PLN (Persero) during the 2010–2024 period using semiannual data. The financial ratios examined include Liquidity (Quick Ratio), Solvency (Debt to Equity Ratio), Activity (Receivable Turnover), and Profitability (Return on Equity). The company’s financial performance is proxied by Return on Assets (ROA). A quantitative approach is applied using secondary data obtained from PT. PLN (Persero)’s financial reports, analyzed with multiple linear regression using Eviews 12 software. The results show that simultaneously, the four financial ratios significantly affect ROA. Partially, only Receivable Turnover and Return on Equity have a positive and significant effect on financial performance, while Quick Ratio and Debt to Equity Ratio show no significant influence. These findings indicate that the efficiency of receivables management and the utilization of equity capital play a dominant role in improving the financial performance of PT. PLN (Persero).